Analisis Pasar Regional Kawasan Asia Timur (China, Hong Kong, Jepang, dan Korea Selatan) dalam Hubungannya dengan Pasar Dunia - Roida, Herlina Yoka; Sukamto, Utomo; Sunarjanto, N. Agus (Jurnal Widya Manajemen & Akuntansi, 2005)
This paper draws the prospect of regionalism among financial market in East Asia (China, Hong Kong, Japan and South Korea). The first part examines the correlation among them that lead to regional integration. The second part shows the possibility of integration or segmentation between East Asia countries and world. The next part, tries to draw whether last financial crises 1997 gave different result to the integration process.